Allelopathic Effect of Solid Bamboo (Dendrocalamus stocksii Munro.) on Cowpea (Vigna unguiculata) - Rawat, Pravin; Narkhede, S. S.; Rane, A. D.; Mhaiske, V. M.; Dalvi, V. V. (Indian Forester, 2018)
To assess the allelopathic effect of Dendrocalamus stocksii Munro. on growth and yield of cowpea (Vigna unguiculata), leaves leachate (25, 50, 75 and 100 per cent concentration) was prepared by soaking dry leaves in tap water for 24 hours in a ratio of 1:10 weight by volume. Results revealed that the concentration-dependent inhibitory effect of leachate on germination, radicle and plumule length of cowpea. However, the mild concentration of leachate (25%) exceptionally stimulated the radicle length in laboratory conditions. In prepared nursery beds inside the poly house, number of pods per plant, number of seeds per pod, seed yield per plant and grain yield ha-1 were significantly reduced by the leachate of higher concentrations (75 and 100%) as compared to control, whilst its effect on straw yield per ha-1 was nonsignificant.